The COVID long-haulers: A letter to the Editor - Paracha, Anousheh Awais; Arshad, Muhammad Sameer; Muhammad Azam (Journal of the Pakistan Medical Association, 2022)
Sir/Madam, Corona Virus disease 2019 (COVID-19) is a global pandemic that has affected over 174 million people and claimed over 4 million lives as of July 2021. (1) However, an aspect often overlooked is long COVID which includes signs and symptoms that develop or continue to persist in patients after acute COVID-19. (2) This has multi-organ system effects including cardiovascular, neurologic, pulmonary, psychiatric, and dermatologic manifestations (3). In a recent study conducted by H.E. Davis et al., Davis and colleagues surveyed 3762 patients with confirmed or suspected long COVID-19. The results showed the prevalence of 203 symptoms spanning over 10 organ systems. (4) The current guidelines place great emphasis on controlling the spread of this infection. While this is imperative, the long-term effects are often over-looked. Evidence shows that patients exhibit higher rates of morbidity and mortality in the six months following diagnosis of acute COVID-19 infection. (4) Long Covid has affected a significant number of health-care workers having a direct impact on the health system. Individuals who were physically fit and active prior to the infection find it increasingly challenging to perform basic daily tasks owing to brain fog.(5) The paucity of evidence across online databases regarding management of long COVID shows the lack of attention given to this factor.